The Politics of Riau Malay Identity in the Implementation of Local Democracy - Muhammad Rafi; Titin Purwaningsih; Syed Agung Afandi; Agus Priyanto (Universitas Muhammadiyah Malang, 2020)
This article looks at the existence of the use of the Malay identity used by regional head candidates in the 2013 Riau Province gubernatorial election. The research method used in this research is the literature study method by analyzing various journals that discuss identity politics and the use of identity in the head election. The results show that in the process, regional representative politics is a strategy that has significance for the victory of Annas Maamun and Arsyad Juliandi Rachman. However, this strategy also needs to be supported by ethnic identity politics for the Riau Coastal and Riau Malay ethnic groups. Thus, this confirms that the use of Riau Malay identity in the implementation of local democracy still serves as an additional strategy in winning the regional head elections in Riau Province.